Incidence of Congenital Heart Disease in Jordanian Children Born at Jordan University Hospital; a Seven-Year Retrospective Study - Al-ammouri, Iyad; Ayoub, Fares; Tutunji, Laila (Jordan Medical Journal, 2016)
Objective: The purpose of this study is to report the incidence of congenital heart disease diagnosed in children born at Jordan university hospital over seven year period. Objective: The purpose of this study is to report the incidence of congenital heart disease diagnosed in children born at Jordan University Hospital over seven-year period. Methods: All echocardiographic studies performed for babies between August 2007 and November 2014 were reviewed. In addition, children who were diagnosed with congenital heart disease in outpatient department, and were born at Jordan University Hospital during the same period were included in the analysis. Number of newborns was determined from hospital data base. We report incidence, diagnoses, and age at diagnosis. Results: Of 31,078 live births, we found 383 (12.3/1000 live birth) patients with congenital heart disease, 52% were males. In 268 patients (70%), the diagnosis was made in the neonatal period, including 16 patients with prenatal diagnosis that was confirmed after birth. In the remaining 115 patients (30%), the diagnosis was made in the outpatient department at a mean age of 7±11 months. The most common diagnosis was ventricular septal defect (43%), followed by atrial septal defect (20%). Cyanotic heart disease accounted for 11% of all congenital heart disease. Conclusion: Congenital heart disease is present in 12.3/1000 Jordanian live births. It is likely that this incidence, although slightly higher than reported incidence worldwide, is an underestimate of the true incidence in Jordan due to under-diagnosis of asymptomatic lesions, presentation of patients to other institutions, or premature death without diagnosis. A national registry for congenital heart disease is needed to provide more accurate incidence, and help plan national health care policies.